IMPLEMENTASI KEBIJAKAN JKN OLEH PEMBERI PELAYANAN KESEHATAN DI KABUPATEN KEPULAUAN ANAMBAS - Irawati Sagala; Laksono Trisnantoro; Retna Siwi Padmawati (Journal of Health Service Management, 2016)
Background: Anambas Islands Regency is a district that iscategorized as a DTPK area. In the health context, rural andremote areas are often associated with limited public transportation,poor road infrastructure, long distances to health carefacilities and difficulties in recruiting and retaining healthworkers. As a result there is a significant impact on the provisionof adequate health services. The availability of insufficient resourcesat every health facility in Anambas Islands Regency isalso an obstacle because in implementing JKN every healthfacility in Anambas Islands Regency must meet thecredentialing requirements set by BPJS Kesehatan.Objective: Analyzing the implementation of JKN policies byhealth service providers in Anambas Islands Regency. Methods: Descriptive research with qualitative methods usinga single case study design Results: Implementation of policy NHI by health care providersboth in health centers and hospitals are still many haveconstraints such as limited power specialist, especially inhospitals, general practitioners definitive still lacking in somehealth facilities, the limited infrastructure in health centers andhospitals that cause will not want the patient should be referred.This adds to the burden of transportation costs to society asocean freight rates are quite expensive though some things canbe addressed as a problem of information and improvement ofbureaucratic structures, but it can not prevent the public to bereferred.Conclusions: The implementation of the JKN policy is notsuitable for implementation in Anambas Islands Regency as aDTPK area because the benefits received by the communityfrom JKN are limited due to the many obstacles faced by healthservice providers.